(3QSGdI aj JUMjM daXI GdRfOjb hJMbjb eYfGg GdObjbs - (3GdJhbGOj GdESJGfHhdj GdYKeGfj GdMfaj, GHf ceGd HGTG, ceGd HGTG RGOg, TeS GdOjf, CMeO Hf SdjeGf Hf ceGd HGTG, (B940 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hdj GdJhajb hHYO gPg QSGdI eYehdI aj JUMjM daX GdRfOjb hJhVjM eYfGg GdObjb afbhd daXI GdRfOjb aGQSj eYQHs
(3BNQgG (B:s
(3cja jOYj dfaSg cYHG TGeNG aj Yde GdaJhi hdG jSJMj ef GdMdGjb Ch bOeG QGSNG aj Yed GdJbhi hdG jNGa ef GdNGdbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 133s
(3eYLe GdeDdajf (B1 / 148s
(3TPQGJ GdPgH (B8 / 238s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds